2017
DOI: 10.1074/mcp.m116.066720
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Age-specific Variability of Plasma Proteins in Healthy Neonates, Children and Adults

Abstract: Human blood plasma is a complex biological fluid containing soluble proteins, sugars, hormones, electrolytes, and dissolved gasses. As plasma interacts with a wide array of bodily systems, changes in protein expression, or the presence or absence of specific proteins are regularly used in the clinic as a molecular biomarker tool. A large body of literature exists detailing proteomic changes in pathologic contexts, however little research has been conducted on the quantitation of the plasma proteome in age-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 22 publications
5
45
0
Order By: Relevance
“…The SWATH Acquisition Microapp 2.0 in PeakView 2.2 (SCIEX) was used to create a spectral library file. This local library was extended using the R package SwathXtend (version 2.3) with a published SWATH dataset of healthy human plasma . The extended library was used for all subsequent SWATH analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SWATH Acquisition Microapp 2.0 in PeakView 2.2 (SCIEX) was used to create a spectral library file. This local library was extended using the R package SwathXtend (version 2.3) with a published SWATH dataset of healthy human plasma . The extended library was used for all subsequent SWATH analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This local library was extended using the R package SwathXtend (version 2.3) [24] with a published SWATH dataset of healthy human plasma. [25] The extended library was used for all subsequent SWATH analysis. Processing settings for the SWATH Microapp: two peptides per protein, three transitions per peptide, peptide confidence threshold corresponding to 1% global FDR, and FDR threshold of 1% was used.…”
Section: Data Processingmentioning
confidence: 99%
“…Until validated these should be considered possible anomalies due to variations at the population level or from longitudinal changes or even from poorly characterized and unsuitable proteotypic peptides. Recent useful examples in the literature have considered changes with maturation and hereditary differences on the basis of the studies of twins . As a simpler directive, it is useful to recognize the depletion targets by their different aliases.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis revealed that the levels of these six housekeeping genes between the groups have significant differences between the control groups ( Supplementary Figure 1 and Supplementary Table 1). These differences can only be attributed to the age, so far, only a couple of studies have compared the levels of proteins in blood samples between children and adults 29,30 , in those cases, they observed also a significant differential expression levels of more than 100 proteins across the ages. Later we measure the levels of Rb mRNA into the three groups' pediatric controls, patients and adults' controls.…”
Section: Validation Of the Identified Housekeeping Genesmentioning
confidence: 99%